(untitled) (Research, Society and Development, 2021)
Odontogenic tumors (OT) form a group of lesions with different histological types and clinical aspects, which can vary from hamartomas to malignant lesions, thus presenting a variety of clinical manifestations. Despite the different clinical behaviors, OT change the morphology of the affected tissues, generating an aesthetic and functional impairment to the patient, which, without treatment, can make it incapacitating depending on the aggressiveness of the tumor. The objective of the work is to report a case of a patient with facial deformity due to an ameloblastoma in the mandible treated with enucleation. Case report: young patient, with complaints of snapping jaws after eating and progressive facial deformity. On physical examination, there was an increase in extraoral volume at the right, intraoral mandibular angle in the cheek mucosa and retromolar tissue causing bitening of the mucosa. Radiographic examination revealed a radiolucent, unilocular image, covering the region of the mandibular body up to the mandibular ramus. The patient underwent puncture, biopsy and installation of a decompression device in the region, which remained in position for 8 months, without the expected success. With the diagnosis of ameloblastoma, it was decided to perform enucleation and curettage of the lesion, which showed good therapeutic efficacy by returning the patient to the previous facial pattern and restoring masticatory functions. Conclusion: The impact of odontogenic tumors on the quality of life of patients is significant and their therapeutics must be established taking into account the type of tumor, its location and aggressiveness, in order to reestablish the functions of the stomatognathic system in the best possible way.